Are loneliness and social isolation equal threats to health and well-being? An outcome-wide longitudinal approach - Joanna H. Hong; Julia S. Nakamura; Lisa F. Berkman; Frances S. Chen; Koichiro Shiba; Ying Chen; Eric S. Kim; Tyler J. VanderWeele (Elsevier, 2023)
The detrimental effects of loneliness and social isolation on health and well-being outcomes are well documented. In response, governments, corporations, and community-based organizations have begun leveraging tools to create interventions and policies aimed at reducing loneliness and social isolation at scale. However, these efforts are frequently hampered by a key knowledge gap: when attempting to improve specific health and well-being outcomes, decision-makers are often unsure whether to target loneliness, social isolation, or both. Filling this knowledge gap will inform the development and refinement of effective interventions. Using data from the Health and Retirement Study (13,752 participants (59% women and 41% men, mean [SD] age = 67 [10] years)), we examined how changes in loneliness and social isolation over a 4-year follow-up period (from t0:2008/2010 to t1:2012/2014) were associated with 32 indicators of physical-, behavioral-, and psychosocial-health outcomes 4-years later (t2:2016/2018). We used multiple logistic-, linear-, and generalized-linear regression models, and adjusted for sociodemographic, personality traits, pre-baseline levels of both exposures (loneliness and social isolation), and all outcomes (t0:2008/2010). We incorporated data from all participants into the overall estimate, regardless of whether their levels of loneliness and social isolation changed from the pre-baseline to baseline waves. After adjusting for a wide range of covariates, we observed that both loneliness and social isolation were associated with several physical health outcomes and health behaviors. However, social isolation was more predictive of mortality risk and loneliness was a stronger predictor of psychological outcomes. Loneliness and social isolation have independent effects on various health and well-being outcomes and thus constitute distinct targets for interventions aimed at improving population health and well-being.